2020
DOI: 10.1186/s12891-020-03212-6
|View full text |Cite
|
Sign up to set email alerts
|

Reverse wedge effect following intramedullary nailing of a basicervical trochanteric fracture variant combined with a mechanically compromised greater trochanter

Abstract: Background: To introduce an unreported intraoperative complication in intramedullary nailing (IN) of an anatomically reduced trochanteric fracture variant characterized by a basicervical fracture line and coronally disrupted greater trochanter (GT). Methods: A total of 414 trochanteric fractures (TF) treated with intramedullary nails from 2013 to 2017 were included in this study. After analysis of intraoperative fluoroscopy data, 33 cases, including 21 females and 12 males, with a mean age of 72.5 years (33 to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…During the surgery, anteromedial calcar fracture gapping was frequent. Zhang et al [ 31 , 32 ] reported that an inferior medial gap (mean and standard deviation, 9.2 ± 4.6 mm) appears during intramedullary nailing in basicervical trochanteric fractures, called the reverse wedge effect. In addition, inferior placement of the guidewire is beneficial for acquiring an ideal Cal-TAD.…”
Section: Discussionmentioning
confidence: 99%
“…During the surgery, anteromedial calcar fracture gapping was frequent. Zhang et al [ 31 , 32 ] reported that an inferior medial gap (mean and standard deviation, 9.2 ± 4.6 mm) appears during intramedullary nailing in basicervical trochanteric fractures, called the reverse wedge effect. In addition, inferior placement of the guidewire is beneficial for acquiring an ideal Cal-TAD.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the conception of the wedge effect, Zhang et al proposed the “reverse wedge effect” during intraoperative fracture reduction and fixation in a recent issue of the journal [ 8 ]. The reverse wedge effect is described as “the reaming/intramedullary nail(IN) insertion generated internal rotation of the cephalocervical fragment and an inferiorly oriented gap at the primary fracture line (basicervical region)”.…”
Section: Main Textmentioning
confidence: 99%
“…2 and 3 ). Unfortunately, this issue has not been explored in this cohort with a reverse wedge effect [ 8 ].
Fig.
…”
Section: Main Textmentioning
confidence: 99%
“…15 Otro desplazamiento posible, aunque poco frecuente, es que, luego de introducir el clavo, se produzca un desplazamiento en valgo de la fractura "efecto cuña reverso". 16 Este tipo de desplazamiento secundario está descrito principalmente en las fracturas con trazo basicervical. Ante esta situación, las posibilidades son: introducir un gancho de hueso o "clamp colineal" y, de esta forma, generar una tracción lateral desde la cortical medial del cuello femoral.…”
unclassified
“…Ante esta situación, las posibilidades son: introducir un gancho de hueso o "clamp colineal" y, de esta forma, generar una tracción lateral desde la cortical medial del cuello femoral. 16 figura 5. a. Imagen radioscópica de perfil en la que se evidencia la caída posterior del fragmento proximal y el solapamiento de las corticales, lo que imposibilita la reducción cerrada. b y c. Introducción de una clavija de 3 mm en el foco y reducción del desplazamiento.…”
unclassified